Complete chloroplast genome of Stephania tetrandra (Menispermaceae) from Zhejiang Province: insights into molecular structures, comparative genome analysis, mutational hotspots and phylogenetic relationships - Dong, Shujie; Ying, Zhiqi; Yu, Shuisheng; Wang, Qirui; Liao, Guanghui; Ge, Yuqing; Cheng, Rubin (BMC genomics, 2021)
The Stephania tetrandra S. Moore (S. tetrandra) is a medicinal plant belonging to the family Menispermaceae that has high medicinal value and is well worth doing further exploration. The wild resources of S. tetrandra were widely distributed in tropical and subtropical regions of China, generating potential genetic diversity and unique population structures. The geographical origin of S. tetrandra is an important factor influencing its quality and price in the market. In addition, the species relationship within Stephania genus still remains uncertain due to high morphological similarity and low support values of molecular analysis approach. The complete chloroplast (cp) genome data has become a promising strategy to determine geographical origin and understand species evolution for closely related plant species. Herein, we sequenced the complete cp genome of S. tetrandra from Zhejiang Province and conducted a comparative analysis within Stephania plants to reveal the structural variations, informative markers and phylogenetic relationship of Stephania species. The cp genome of S. tetrandra voucher ZJ was 157,725 bp, consisting of a large single copy region (89,468 bp), a small single copy region (19,685 bp) and a pair of inverted repeat regions (24,286 bp each). A total of 134 genes were identified in the cp genome of S. tetrandra, including 87 protein-coding genes, 8 rRNA genes, 37 tRNA genes and 2 pseudogene copies (ycf1 and rps19). The gene order and GC content were highly consistent in the Stephania species according to the comparative analysis results, with the highest RSCU value in arginine (1.79) and lowest RSCU value in serine of S. tetrandra, respectively. A total of 90 SSRs have been identified in the cp genome of S. tetrandra, where repeats that consisting of A or T bases were much higher than that of G or C bases. In addition, 92 potential RNA editing sites were identified in 25 protein-coding genes, with the most predicted RNA editing sites in ndhB gene. The variations on length and expansion extent to the junction of ycf1 gene were observed between S. tetrandra vouchers from different regions, indicating potential markers for further geographical origin discrimination. Moreover, the values of transition to transversion ratio (Ts/Tv) in the Stephania species were significantly higher than 1 using Pericampylus glaucus as reference. Comparative analysis of the Stephania cp genomes revealed 5 highly variable regions, including 3 intergenic regions (trnH-psbA, trnD-trnY, trnP) and two protein coding genes (rps16 and ndhA). The identified mutational hotspots of Stephania plants exhibited multiple SNP sites and Gaps, as well as different Ka/Ks ratio values. In addition, five pairs of specific primers targeting the divergence regions were accordingly designed, which could be utilized as potential molecular markers for species identification, population genetic and phylogenetic analysis in Stephania species. Phylogenetic tree analysis based on the conserved chloroplast protein coding genes indicated a sister relationship between S. tetrandra and the monophyletic group of S. japonica and S. kwangsiensis with high support values, suggesting a close genetic relationship within Stephania plants. However, two S. tetrandra vouches from different regions failed to cluster into one clade, confirming the occurrences of genetic diversities and requiring further investigation for geographical tracing strategy. Overall, we provided comprehensive and detailed information on the complete chloroplast genome and identified nucleotide diversity hotspots of Stephania species. The obtained genetic resource of S. tetrandra from Zhejiang Province would facilitate future studies in DNA barcode, species discrimination, the intraspecific and interspecific variability and the phylogenetic relationships of Stephania plants.